Analisis Faktor Motivasi Kerja TKA (Tenaga Kerja Asing) pada Hotel Berbintang di Kecamatan Kuta Selatan Kabupaten Badung Bali - Wacana Sari, Putu Yunita; Wiranatha, Agung Suryawan; Sukaatmadja, I Putu Gde (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 02, Januari 2021DO - 10.24843/JUMPA.2021.v07.i02.p14, 2021)
The tourism sector in the southern part of Bali, especially in South Kuta District, Badung Regency, Bali has been significantly developed with the development of the star-rated hotels. The development of this star-rated hotels certainly opened working opportunities for the foreign labour. In accordance with the increasing number of those foreign labour therefore, this study was conducted with the aim of analysing the factors that motivate foreign labour to work at star-rated hotels in the South Kuta District, Badung Regency, Bali. The data collection techniques used were limited interviews, documentation and literature study. The population are all expatriates who work at star-rated hotels in South Kuta District, Badung Regency, Bali based on IMTA data from the Badung Regency Industry and Manpower Office for the 2017-2018 period, with a sample size of 100 respondents selected by quota sampling. The instrument in the form of a questionnaire was used to obtain respondent data. The data analysis technique used in this research is factor analysis. The result of this study showed that the twenty variables of this study were classified into 4 (four) factors, namely: Compensational Factor (Payment and Status), Interpersonal Relationship Factor (Interpersonal Relations), Work Factor (Work Itself), and Development Factor (Personal Development). These four factors were the motivation factors for foreign labour to work at star- rated hotel in South Kuta District, Badung Regency, Bali. Keywords: Foreign Labour, Working Motivation, Factor Analysis